1993
DOI: 10.1161/01.hyp.21.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of vasoconstrictor response by a noncalcemic analogue of vitamin D3.

Abstract: To clarify the effects of active vitamin D 3 on pressor and vascular responses to vasoconstrictor substances, we studied pressor responses to the intravenous injection of norepinephrine or angiotensin II (Ang II) and vasoconstrictor responses to norepinephrine. Sprague-Dawley rats were given 1,25 -dihydroxyvitamin D 3 subcutaneously (200 ng/kg per day) for 14 days. The administration of 1,25-dihydroxyvitamin D, augmented the pressor responses to norepinephrine and Ang II in conscious rats and was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that vitamin D 3 supplementation, when given at pharmacological doses, increases the vascular tonus in rats [18][19][20] and that this effect may be independent of the increase in the vascular calcium content [21,22]. These observations also hold true in humans.…”
Section: Discussionmentioning
confidence: 90%
“…It has been demonstrated that vitamin D 3 supplementation, when given at pharmacological doses, increases the vascular tonus in rats [18][19][20] and that this effect may be independent of the increase in the vascular calcium content [21,22]. These observations also hold true in humans.…”
Section: Discussionmentioning
confidence: 90%
“…In SHR, 1,25(OH) 2 D 3 treatment increased the active stress response of resistance arteries to norepinephrine and arginine vasopressin, without changing sensitivity [41]. Moreover, the perfusion pressure induced by norepinephrine was significantly elevated in mesenteric vascular bed from 1,25(OH) 2 D 3 -treated, as well as nonhypercalcemic vitamin D analog (22-oxacalcitriol)-treated rats compared to controls [42].…”
Section: Vasoactivitymentioning
confidence: 88%
“…The receptor of calcitriol has been shown in vascular smooth muscle cells [64, 65], and calcitriol also stimulates the capture of calcium from the extracellular space [66, 67, 68, 69, 70]. Moreover, treatment with calcitriol increases the force-generating capacity of isolated resistance arteries [66, 69]and enhances the pressor response to norepinephrine and angiotensin II in vivo [71]. …”
Section: Introductionmentioning
confidence: 99%